Ketahanan hidup 5 tahun pada pasien kanker payudara - Evi Susanti Sinaga; Riris Andono Ahmad; Susanna Hilda Hutajulu (Berita Kedokteran Masyarakat (BKM), 2017)
Analysis of 5-year survival of patients treated for breast cancer at Sardjito Hospital in Yogyakarta province, IndonesiaPurposeThis study aimed to assess the length of life of breast cancer patients as well as factors related to the prognosis of survival of patients.MethodsThis research was a retrospective study. Samples in this study were patients with breast cancer who were first diagnosed with breast cancer from January 1, 2009 until December 31, 2009 at the Dr. Sardjito Hospital, Yogyakarta. The Kaplan Meier method was used for the data analysis, and final factors were reviewed and those that showed significant association were entered in a Cox regression model. Calculations were performed in Stata 12.0.ResultsResults showed the 5 year survival rate was 51.07%. In bivariate analysis, there was a correlation between the age of diagnosis, education, clinical stage, tumor size and tumor location on 5-year survival in patients with breast cancer. For multivariate analysis, age of diagnosis had the most powerful correlation (HR = 3.73; 95% CI = 1.0 to 13.6) on survival (p = 0.046).ConclusionSurvival rates of women with breast cancer aged less than 50 years were lower. Young women with breast cancer tended to have more aggressive breast cancer growth and recurrence risks were greater. Efforts are needed for early detection of breast cancer to improve survival in breast cancer patients.